1982
DOI: 10.1007/bf03189627
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of hepatic drug metabolism in patients with acute viral hepatitis

Abstract: Hepatic drug metabolism in patients with acute viral hepatitis was investigated under different conditions: pregnancy, postpartum, non-pregnancy, and among males. Liver function tests were altered in all of these conditions. The relationship between in vivo and in vitro drug metabolism was studied in twenty-two patients using diagnostic liver needle biopsies by comparing the drug metabolising enzymes (aminopyrine-N-demethylase and bilirubin-UDP-glucuronyl transferase) in these biopsies with the elimination kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The toxic effect of paracetamol is due to a highly reactive arylating metabolite that is formed when the capacity to conjugate the drug is exceeded. The formation of the toxic metabolite is dependent on the availability of cytochrome P-450, which is reduced in severe hepatitis (Farrell et al 1978(Farrell et al , 1979Gabrielle et al 1977;Narang et al 1982;Schoene et al 1972) and also on the liver content of glutathione, which binds and inactivates the toxic metabolite (Mitchell et al 1974). Thus, it remains an open question whether or not the concentrations of the reactive metabolite are increased in patients with hepatitis in continuous paracetamol medication.…”
Section: Discussion and Therapeutic Implicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…The toxic effect of paracetamol is due to a highly reactive arylating metabolite that is formed when the capacity to conjugate the drug is exceeded. The formation of the toxic metabolite is dependent on the availability of cytochrome P-450, which is reduced in severe hepatitis (Farrell et al 1978(Farrell et al , 1979Gabrielle et al 1977;Narang et al 1982;Schoene et al 1972) and also on the liver content of glutathione, which binds and inactivates the toxic metabolite (Mitchell et al 1974). Thus, it remains an open question whether or not the concentrations of the reactive metabolite are increased in patients with hepatitis in continuous paracetamol medication.…”
Section: Discussion and Therapeutic Implicationsmentioning
confidence: 98%
“…Adequate knowledge on the elimination of aspirin in liver disease appears to be lacking (Brodie et al 1959;Menguy et al 1972). It has been shown that the hepatic activity of cytochrome P-450 and other drug metabolising enzyme systems is reduced in patients with severe infectious hepatitis, while that of some other enzyme systems is unchanged (Farrell et al 1978(Farrell et al , 1979Gabrielle et al 1977;Narang et al 1982;Schoene et al 1972). Likewise, the elimination rate of cefoperazone, hexobarbitone, antipyrine, valproic acid, pethidine (meperidine), triamterene and theophylline is slower than normal in patients with hepatitis (BelaiefT et al 1981 ;Breimer et al 1975;Burnett et al 1976;Gugler & von Unruh 1980;McHorse et al 1975;Mutschler et al 1983;Staib et al 1980), while that of pindolol, oxazepam, warfarin and lignocaine (lidocaine) is normal (Ohnhaus et al 1982;Shull et al 1976;Williams et al 1976a,b).…”
mentioning
confidence: 98%
“…Such changes have also been found during the course of acute viral hepatitis. The clearance of the model drug of hepatic oxidative metabolism, antipyrine (phenazone) was found to be decreased by 35±70% during the acute phase of viral hepatitis [3,4,5]. Impaired hepatic metabolism may also occur in non-hepatic viral diseases such as in¯uenza and in infection with the human immunode®-ciency virus (HIV), possibly due to the induction of interferon production [6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 97%
“…During other liver disease states, such as septic cholestasis, obstructive cholestasis, and alcoholic and viral hepatitis, human and rodent studies have demonstrated alterations in cytochrome P450-mediated drug metabolism, transport, and pharmacokinetics (Forrest et al, 1977;Farrell et al, 1978Farrell et al, , 1979Narang et al, 1981Narang et al, , 1982Narang et al, , 1985Figg et al, 1995;Westphal and Brogard, 1997;Kubitz et al, 1999;Nadai et al, 2001;Congiu et al, 2002). However, there is little information on the effect of NAFLD on these same parameters.…”
mentioning
confidence: 99%